Stratigraphy of the fluvial deposits of the Salado river basin, Buenos Aires Province: Lithology, chronology and paleoclimate. (July 2015) - Fucks, E.; Pisano, M.F.; Huarte, R.A.; Di Lello, C.V.; Mari, F.; Carbonari, J.E.
Abstract: The regional landscape of the Salado depression is related to weathering, eolian and fluvial processes generated under different climatic conditions. Although during most of the Holocene the climatic conditions were warm and humid, previously, a vast plain dominated by deflation processes and enhanced by weathering processes was developed in an arid environment. Fluvial deposits produced afterwards are continuous and lithologically homogeneous, which allows differentiation and characterization of the entire stratigraphic sequence. The stratigraphic units of this area, closely related to the paleoclimatic conditions, are recognized and characterized. Three lithostratigraphic units of fluvial origin (Members) and two paleosols have been differentiated. The first ones were grouped in the Luján Formation. Some of the units are related to other ones previously recognized in this area (La Chumbiada Member and La Pelada Geosol), but others have no similarity or relationship with previously known units (Gorch and Puente Las Gaviotas Members, and Frigorífico Belgrano Geosol). Radiocarbon ages suggest that the fluvial sequences were deposited after the glacial maximum, corresponding to MIS 1, except for the basal levels of the lower member which is late Late Pleistocene. Although the general paleoclimatic conditions were related to warm and humid climate, events related to water deficits were also recognized, which could be related to the Younger Dryas, the middle Holocene and the late Holocene. Highlights: We analysed the fluvial deposits of the middle basin of the Salado river with ages of Late Pleistocene–Holocene. Analyzes performed allowed us to establish the environmental conditions prevailing in the area at the end of the Quaternary. We proposed a new stratigraphic scheme made up of lithoestratigraphic and pedoestratigraphic units, and radiocarbon ages.